STRATEGI KEPEMIMPINAN KEPALA SEKOLAH DALAM MENINGKATKAN KINERJA GURU DI ERA DIGITALISASI - Edison Rumbiak; Petrus Irianto; Robert Masreng; Ida M. Hutabarat; Yulius Mataputun; Diki Kurniawan (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
This research aims to analyze the principal's leadership strategies in improving teacher performance in the digitalization era at SMP Negeri 2 Tiom, Lanny Jaya Regency, Highland Papua Province. The focus includes strategies for fostering morale and confidence, providing guidance and direction, the role of modeling, and providing inspiration, as well as identifying supporting factors, inhibitors, and the impact of these strategies. This study employs a qualitative approach with a case study design. Data were collected through in-depth interviews with eight informants (principal, teachers, operator, committee, and students), participant observation, and documentation studies. Data analysis was conducted using the Miles and Huberman interactive model, consisting of data condensation, data display, and conclusion drawing. The results indicate that the principal implements a